2017
DOI: 10.3390/s17081720
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Robot Interfaces and Operator Situational Awareness: Study of the Impact of Immersion and Prediction

Abstract: Multi-robot missions are a challenge for operators in terms of workload and situational awareness. These operators have to receive data from the robots, extract information, understand the situation properly, make decisions, generate the adequate commands, and send them to the robots. The consequences of excessive workload and lack of awareness can vary from inefficiencies to accidents. This work focuses on the study of future operator interfaces of multi-robot systems, taking into account relevant issues such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
(27 reference statements)
1
23
0
3
Order By: Relevance
“…Our results Results of [24] Results of [25] Results of [26] Results of [27] Results of [28] F I G U R E 1 6 Comparison between NASA task load index (NASA-TLX) percentage decrease in our results and reported results of somewhat similar experiments TLX. Furthermore, in [24], it has been reported that the perceived SA for controlling five UAVs is equal to 5.3.…”
Section: 27%mentioning
confidence: 59%
See 1 more Smart Citation
“…Our results Results of [24] Results of [25] Results of [26] Results of [27] Results of [28] F I G U R E 1 6 Comparison between NASA task load index (NASA-TLX) percentage decrease in our results and reported results of somewhat similar experiments TLX. Furthermore, in [24], it has been reported that the perceived SA for controlling five UAVs is equal to 5.3.…”
Section: 27%mentioning
confidence: 59%
“…As depicted in Figure 17, our result has a good balance in terms of increasing SAGAT and decreasing NASA- Our results Results of [24] Results of [25] Results of [26] Results of [27] Results of [28] 19.57%…”
Section: Subjective Measuresmentioning
confidence: 68%
“…Some important issues discovered in the multirobot missions were the causes of accident, the inefficiencies in the management of resources and the limitations of the commanding interface. In fact, the analysis performed in this work was the starting point for the design of an adaptive and immersive interface in a later one (Roldán et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges faced by multi-robot operators can be addressed by developing immersive and adaptive interfaces. The former apply virtual or augmented reality to introduce operators into the environment, improving their perception of the agents and their mission awareness [6]. The latter take on some of the operator's tasks and provide the worker with the most relevant information and the most suitable decisions available, thus reducing the operators' workload and improving their performance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most promising strategies to address these issues involve the development of adaptive interfaces: selection of relevant information, adaptation to operator preferences, and guidance of operator attention [11]. In previous works, the positive impact of immersion and prediction on operator workload, situational awareness, and performance was demonstrated in a mission with multiple drones [6] and another mission with ground, aerial, and manipulator robots [12].…”
Section: Introductionmentioning
confidence: 99%